Detection of Mogibacterium timidum in subgingival biofilm of aggressive and non-diabetic and diabetic chronic periodontitis patients - Casarin, Renato Corrêa Viana; Saito, Daniel; Santos, Vanessa Renata; Pimentel, Suzana Peres; Duarte, Poliana Mendes; Casati, Márcio Zaffalon; Gonçalves, Reginaldo Bruno (Brazilian journal of microbiology, 2012)
The aim of the present study was to evaluate the frequency of detection of Mogibacterium timidum in subgingival samples of subjects with generalized aggressive periodontitis (GAgP) and uncontrolled diabetic and non-diabetic subjects with generalized chronic periodontitis (GChP). 48 patients with GAgP, 50 non-diabetic and 39 uncontrolled (glycated hemoglobin >7%) type 2 diabetic subjects with GChP were enrolled in this study. Subgingival biofilm were collected from deep pockets (probing depth > 7 mm). After DNA extraction, M. timidum was detected by Nested Polymerase Chain Reaction and chi-square test was used to data analysis (p>0.05). There were no differences in the frequency of detection of M. timidum between subjects with GAgP (35%) and non-diabetic subjects with GChP (40%) (p>0.05). The frequency of detection of M. timidum was significantly higher in deep pockets of diabetic subjects with GChP (56%) when compared to GAgP (p<0.05), but similar to non-diabetic subjects with GChP (p>0.05). The frequency of detection of M. timidum was higher in subjects GChP presenting uncontrolled type 2 diabetes mellitus, when compared to GAgP subjects.